Passivity-Sliding Mode Control of Uncertain Chaotic Systems with Stochastic Disturbances - Zhumu Fu; Leipo Liu; Xiaohong Wang (Journal of Control Science and Engineering)
This paper is concerned with the stabilization problem of uncertain chaotic systems with stochastic disturbances. A novel sliding function is designed, and then a sliding mode controller is established such that the trajectory of the system converges to the sliding surface in a finite time. Using a virtual state feedback control technique, sufficient condition for the mean square asymptotic stability and passivity of sliding mode dynamics is derived via linear matrix inequality (LMI). Finally, a simulation example is presented to show the validity and advantage of the proposed method.